The Role of English Speaking Skills in Career Readiness: Building Information Modeling (BIM) Students - Neng Sri Siti Rahma; Riki Ruswandi; Leny Saili Rahmah (Universitas Sebelas Maret, 2025)
In the era of globalization, English language skills are crucial for career readiness, especially in technical fields such as Building Information Modeling (BIM). However, vocational high school students often face challenges in developing these skills due to curricula that prioritize technical expertise over professional communication. This study examines BIM students' perceptions of the importance of English language skills for their career readiness and the challenges they face in acquiring them. The study collected data using a descriptive, quantitative approach through a questionnaire that had been previously validated by 30 respondents. This was then distributed to 72 BIM students at a public vocational school in Bandung. The results showed that the majority of students (97.3%) recognized a competitive advantage in finding employment due to their English language skills, but 84.7% lacked confidence in using English professionally, largely due to a lack of learning opportunities that fostered confidence in speaking English. Furthermore, 94.4% of students felt that their English lessons did not fully focus on the speaking skills needed in the workplace. These findings highlight the need for vocational education to adopt a more practical and interactive English curriculum that integrates job interview simulations, project presentations, and direct exposure to professional communication in English. This study showed that increasing students' confidence and competence in speaking English can improve their career prospects in an increasingly internationalized job market.